I, Elena de la Cruz: Heresy and Gender in Mexico City, 1568 - Holler, Jacqueline (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
AbstractIn July 1568, a nun was denounced to the episcopal inquisition of Mexico City. Elena de Ia Cruz, was a professed nun in the prestigious Nuestra Senora de la Concepción and a member of one of Mexico's most important families. She was charged with heretical propositions: namely, that she proposed limits to the powers of the papacy and church hierarchy, including Alonso de Montúfar, the archbishop of Mexico.Elena's heretical words also took added meaning from contemporary religious crisis and reform. Some of the nun's conceptions vaguely suggested Lutheranism. More importantly, she seemed to deny the ability of the Council of Trent to carry out its programme of reform. Tridentine reformers were attempting to bring monasteries of women under the control of male religious leaders — and Montúfar was trying to bring regular clergy in general under episcopal governance. Elena's views threatened these efforts.The essay argues that Elena's daring to speak on matters of doctrine was a form of gender treason; she also read forbidden books and attempted to find her own path to salvation. In the late sixteenth century, a woman who took this path was immediately suspect. Beatas, nuns, and laywomen had paid dearly for this error in Spain. Unlike many heretic nuns, though, Elena renounced her beliefs almost immediately when challenged by her abbess, and she showed no courage of conviction before the male inquisitors. Nonetheless, formal charges were prepared and followed through in meticulous detail. In charging Elena, Montúfar was nipping womanly insubordination in the bud, before it could infect the entire convent.But if gender was part of what made Elena so dangerous, it was also what saved her skin. Elena's lawyers were able to use the topos of the weak, ignorant, misled woman to explain their client's deviation from the path of order and obedience. Hispanic gender ideologies made it possible to frame Elena's crime in terms of treason and disorder, but also provided an opportunity for the nun's reincorporation into society. The paper argues that Elena's trial provides an opportunity to examine the ambiguities of gender prescription and what we might call "rôle enforcement". The tension between corporate protection of women and fear of their potential for disorder is played out throughout the trial. Elena's triumph, if such it can be called, is to appeal to the former.